2008
DOI: 10.1016/j.dnarep.2008.04.017
|View full text |Cite
|
Sign up to set email alerts
|

3-Methyladenine DNA glycosylase is important for cellular resistance to psoralen interstrand cross-links

Abstract: DNA interstrand cross-links (ICLs), widely used in chemotherapy, are cytotoxic lesions because they block replication and transcription. Repair of ICLs involves proteins from different repair pathways however the precise mechanism is still not completely understood. Here, we report that the 3-methyladenine DNA glycosylase (Aag), an enzyme that initiates base excision repair at a variety of alkylated bases, is also involved plays a role in the repair of ICLs. Aag−/− mouse embryonic stem cells were shown to be m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…These results indicate that the influence of the sequence context affects both insertion opposite the THF and extension beyond the mismatch, as has been shown for other polymerases (45,46). Importantly, the bypass efficiency of B35DNAP is higher than that of other replicative polymerases, such as yeast pole (6-17%) (46), and comparable to previously reported values for Y family polymerases, including human DNA polymerase η (10-13%), Sulfolobus solfataricus Dpo4 (13-30%), and Escherichia coli DNA polymerase IV (25-40%) (45,47,48).…”
Section: Resultssupporting
confidence: 72%
“…These results indicate that the influence of the sequence context affects both insertion opposite the THF and extension beyond the mismatch, as has been shown for other polymerases (45,46). Importantly, the bypass efficiency of B35DNAP is higher than that of other replicative polymerases, such as yeast pole (6-17%) (46), and comparable to previously reported values for Y family polymerases, including human DNA polymerase η (10-13%), Sulfolobus solfataricus Dpo4 (13-30%), and Escherichia coli DNA polymerase IV (25-40%) (45,47,48).…”
Section: Resultssupporting
confidence: 72%
“…Whether or not this increased sensitivity was the result of impaired removal of interstrand crosslinks or one of the many monoadducts formed by these compounds, however, was not determined. More recent data from the Samson laboratory indicate that MPG (also known as AAG) is important for resistance of mouse embryonic stem cells to psoralen-induced interstrand crosslinks, but not angelicin-induced monoadducts, although the exact molecular process that engages MPG has not been elucidated (9).…”
mentioning
confidence: 99%
“…In 2007, CouvePrivat et al declared that HeLa cells lacking BER proteins human apurinic/apyrimidinic endonuclease (APE1) and/or DNA glycosylase NEIL1 (glycosylases initiating the first step in base excision repair) become hypersensitive to 8-methoxypsoralen after UVA exposure [82]. Somewhat later, it was reported that cells lacking MPG are hypersensitive to cross-linking [83]. In 2009 Zhu et al identified the role of XRCC1 protein, which also represents BER protein family, in binding to cisplatin-DNA ICL [84].…”
Section: Mechanisms Involved In Icl Repairingmentioning
confidence: 98%